DEVELOPMENT OF ZEP QUIZ DIGITAL MEDIA AS A FORMATIVE ASSESSMENT INSTRUMENT ON ARITHMETIC SEQUENCES AND SERIES - Lisfianisa, Syipa; Hasanah, Aan (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Assessment is an essential part of the learning process as it functions to measure students’ abilities and provide feedback for educators. In today’s digital era, the use of technology-based media has become increasingly relevant for both teachers and students. This study aims to develop Zep Quiz digital media as a formative assessment instrument on the topic of Arithmetic Sequences and Series for Grade X students. The research method employed was Research and Development (R&D), consisting of the following stages: Potential and Problems, Data Collection, Product Design, Design Validation, Design Revision, Product Trial, Product Revision, and Final Product. Validation results indicate that the Zep Quiz-based assessment instrument achieved an average validity level of 91.91%, categorized as very valid. A limited trial involving 21 students and 3 teachers at SMAS Daarul Amanah showed practicality results of 86.67% for students and 96.67% for teachers, with an overall average of 91.67%, categorized as very practical. Therefore, it can be concluded that the developed Zep Quiz digital media is feasible to be used as a formative assessment instrument on the topic of Arithmetic Sequences and Series for Grade X.Asesmen merupakan bagian penting dalam proses pembelajaran karena berfungsi untuk mengukur kemampuan peserta didik serta memberikan umpan balik bagi pendidik. Pada era digital saat ini, pemanfaatan media berbasis teknologi menjadi semakin relevan, baik bagi guru maupun peserta didik. Penelitian ini bertujuan untuk mengembangkan media digital Zep Quiz sebagai instrumen asesmen formatif pada materi Barisan dan Deret Aritmetika untuk peserta didik kelas X. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan tahapan: Potensi dan Masalah, Pengumpulan Data, Desain Produk, Validasi Desain, Revisi Desain, Uji Coba Produk, Revisi Produk, dan Produk Akhir. Hasil validasi menunjukkan bahwa instrumen asesmen berbasis Zep Quizmemiliki tingkat kevalidan rata-rata sebesar 91,91% dengan kategori sangat valid. Uji coba terbatas yang melibatkan 21 peserta didik dan 3 guru di SMAS Daarul Amanah menunjukkan hasil kepraktisan sebesar 86,67% pada siswa dan 96,67% pada guru dengan rata-rata 91,67% yang termasuk dalam kategori sangat praktis. Dengan demikian, dapat disimpulkan bahwa media digital Zep Quizyang dikembangkan layak digunakan sebagai instrumen asesmen formatif pada materi Barisan dan Deret Aritmetika kelas X.